Review of the Research on Augmented Reality Maintenance Assistant System of Mechanical System. Issue 6 (January 2021) - Jia, Wenze; Zhu, Junyao; Xie, Lizhong; Yu, Cungui
Abstract: In order to ensure the normal operation of mechanical system and solve the problems of complex structure and insufficient cognition caused by mechanical system updating, the advantages of applying augmented reality technology in the field of fault diagnosis and maintenance are analyzed. Firstly, this paper summarizes the application of augmented reality technology for maintenance assistance cases at home and abroad, analyzes its industry characteristics and application advantages, then summarizes the key technologies of augmented reality, and finally prospects the development trend of the system application.